Growth Performance of Certain Directly Seeded Plants on Mine Spoil in a Dry Tropical Environment, India - Jha, Arvind Kumar; Singh, J. S. (Indian Forester, 1993)
The growth performance of certain directly seeded leguminous trees, non-leguminous trees, leouminous forbs, grasses and crops were evaluated on 12 yr old flat surface coal mine spoil at Jhingurda Colliery, Northern Coal fields Ltd., Singrauli. Out of thirty plant species tried twenty four species showed satisfactory growth performance after one year of seeding. Cajanus cajon showed better growth performance on mine spoil than fertilized Agriculture Farm plots at Barkachha, Mirzapur. For quick revegetation of mine spoil seeding of plant species is a suitable method.